2009
DOI: 10.1189/jlb.0609433
|View full text |Cite|
|
Sign up to set email alerts
|

Lipid droplet formation in leprosy: Toll-like receptor-regulated organelles involved in eicosanoid formation and Mycobacterium leprae pathogenesis

Abstract: A hallmark of LL is the accumulation of Virchow's foamy macrophages. However, the origin and nature of these lipids, as well as their function and contribution to leprosy disease, remain unclear. We herein show that macrophages present in LL dermal lesions are highly positive for ADRP, suggesting that their foamy aspect is at least in part derived from LD (also known as lipid bodies) accumulation induced during ML infection. Indeed, the capacity of ML to induce LD formation was confirmed in vivo via an experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
197
0
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(221 citation statements)
references
References 70 publications
16
197
0
8
Order By: Relevance
“…In addition, Li et al (2011) were able to determine that NEDD4L is a positive regulator of NF-κB which is in agreement with our results. Similarly, the ability of MAP3K8 and PLIN2 to activate the NF-κB pathway has been documented (Chan and Reed, 2005;Cismasiu et al, 2009;Mattos et al, 2010). These direct relationships are supported by results presented here.…”
Section: Gene Expression and Pathway Analysissupporting
confidence: 89%
“…In addition, Li et al (2011) were able to determine that NEDD4L is a positive regulator of NF-κB which is in agreement with our results. Similarly, the ability of MAP3K8 and PLIN2 to activate the NF-κB pathway has been documented (Chan and Reed, 2005;Cismasiu et al, 2009;Mattos et al, 2010). These direct relationships are supported by results presented here.…”
Section: Gene Expression and Pathway Analysissupporting
confidence: 89%
“…2, 3). Earlier reports that C. pneumoniae-or mycobacteria-induced foam cell formation was reduced in TLR2-deficient macrophages [31][32][33] , and the observation that LPS promotes macrophage lipid accumulation 34) , also support this conclusion. To date, the most widely studied potential mechanism for the generation of foam cells in atheroma has been the uptake of oxidised LDL by macrophage scavenger receptors 2) ; however, the results of this and pre-the absence of overt infections.…”
Section: Discussionmentioning
confidence: 57%
“…Our previous data also indicated that Mycobacterium-induced LD formation in infected macrophages depends on bacterial recognition via TLRs. Accordingly, we showed recently that TLR2 and TLR6 pathways are preferentially activated during LD biogenesis triggered by M. bovis BCG and M. leprae infection in macrophages (9,11,12,15).…”
mentioning
confidence: 97%
“…These lipids were initially thought to be derived from M. leprae, such as phthiocerol dimycocerosate/ dimycocerosate and phenolic glycolipid-1 (PGL-1) (6, 7). However, very recently, a more detailed analysis of the lipid metabolism in LL lesions indicated that the foamy aspect is due mostly to the accumulation of host-derived lipids, such as oxidized phospholipids and cholesterol ester (8,9).These lipids were shown to be stored in nonmembrane-bound cytoplasmic organelles known as lipid bodies or lipid droplets (LDs) (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation